Automatic Disentanglement of Motion in Fetal Low Field MRI Scans - Kitzberger, Michael; Silva, Sara Neves; Verdera, Jordina Aviles; Rojas, Diego Fajardo; Uus, Alena; Schulz-Heise, Susanne; Schmidt, Sandy; Schneider, Michael; Story, Lisa; Uder, Michael; Rutherford, Mary; Hutter, Jana (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2025)
Fetal dynamic MRI acquisitions allow insights into fetal motor behaviour, serving as a surrogate for fetal cognitive development. Systematic assessment of these highly temporally resolved 2D images might hence allow novel insights into both normal development and contain crucial information in pathology. Here, we present an automatic deep learning-based assessment for masking of the uterine and fetal structures and fetal and maternal motion quantification tool, applied to 61 low field 0.55T fetal cine MRI datasets acquired between 24 and 40 weeks gestational age at two sites using two different MR contrasts. The lack of cine labels was overcome by imitating cine acquisitions from high-resolution labelled static 3D anatomical balanced steady-state free precession datasets. Results illustrate high segmentation accuracy for the larger uterine structures (mean dice coefficient of 0.86 for the fetal body, 0.88 for the fetal head, 0.61 for the placenta) as well as the ability to detect fetal motion.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Cine; Fetal MRI; Motion assessment

Frequency and impact of enteric hyperoxaluria in pediatric short bowel syndrome: a retrospective single centre study - Schaefer, Jan Thomas; Schulz-Heise, Susanne; Rueckel, Aline; Rauh, Manfred; Jüngert, Jörg; Galiano, Matthias; Meier, Norbert; Wölfle, Joachim; Schiffer, Mario; Hörning, André (Frontiers in Pediatrics, 2023)
Objectives: The survival of pediatric patients with short bowel syndrome has improved in recent years. Enteric hyperoxaluria as a pathophysiological consequence has been hardly addressed so far. It can be associated with nephrolithiasis, nephrocalcinosis or even renal insufficiency. We assessed the prevalence of hyperoxaluria and its pathogenic consequences in a retrospective single centre study over the last 12 years. Methods: We conducted an internal database search for all pediatric patients suffering from short bowel syndrome treated from 2010 to 2022 in the department of pediatric gastroenterology as well as the pediatric nephrology and dialysis unit. Out of 56 patients identified, 26 patients were analysed for etiology of short bowel syndrome, renal excretion of oxalate (24/26), remaining short bowel and large intestinal length as well as further clinical parameters such as eGFR, nephrocalcinosis/urinary stone formation or stool frequency. Results: Hyperoxaluria was detected in 14/26 patients (54%). Nephrocalcinosis was present in four patients. Out of these four patients, hyperoxaluria could be proven (21% of all hyperoxaluric patients) in three cases, one hyperoxaluric patient had nephrolithiasis (7%). In one patient hyperoxaluria lead to end stage renal disease. We found that 80% of patients with volvulus developed enteric hyperoxaluria. None of the investigated factors had an effect on oxalate excretion. Conclusion: Enteric hyperoxaluria is a relevant pathophysiological finding in patients with short bowel syndrome occurring in about 50% of our cohort with multiple pathogenic complications. Regular screening for hyperoxaluria may be implemented in medical care for patients with short bowel syndrome. If necessary, prophylaxis, e.g., dietary advice or metaphylaxis should be initiated.
CRIS-Team Scopus Importer:2023-08-11
Keywords: enteric hyperoxaluria; hyperoxaluria; intestinal failure; kidney stone; nephrolithiasis; pediatric; short bowel syndrome

Ultrasound Localization Microscopy for the Assessment of Microvascular Circulation in Ischemic Perinatal Stroke - Regensburger, Adrian; Wachter, Felix; Denis, Louise; Mandelbaum, Henriette; Schey, Frauke; Bühler, Adrian; Siebenlist, Gregor; Schwarz, Simone; Schulz-Heise, Susanne; Rompel, Oliver; Trollmann, Regina; Wölfle, Joachim; et al. (Stroke, 2024)
CRIS-Team Scopus Importer:2024-11-15
Keywords: diagnostic imaging; microcirculation; neonate; stroke; ultrasound